The Impact of Different Drying Techniques on the Physicochemical and Quality Characteristics of Oil Palm Fruit Mesocarp (Elaeis guineensis) - Vida Gyimah Boadu; Edward Ken Essuman; Gifty Serwaa Otoo; Kate Bigson (International Journal of Food Science)
Drying is one of the traditional means of preserving food. However, various drying methods can influence the nutritional and bioactive constituents of the food product. This study is aimed at evaluating the effect of different drying methods on the proximate composition, physicochemical properties, and minor constituents of palm oil fruit mesocarp. Two varieties of fresh oil palm fruit (dura and tenera) were processed to separate the mesocarp from the other part of the fruit. The fresh fruit mesocarp was divided into five groups and subjected to different drying methods. Proximate and physicochemical characteristics of the oil palm fruit mesocarp were determined. The dried mesocarp had low moisture content (1.49-3.28%), high crude fat content (78.10-90.60%), carbohydrate (4.41-15.12%), crude protein (0.93-3.40%), and ash (0.53-1.15%). The free fatty acid (FFA) (1.06-3.54) and acid value (AV) (2.17 to 8.83 mgKOH/g) were lower because the samples were heated at 100°C for 30 min. The lower pH, FFA, AV, titratable acidity, moisture content, and high antioxidant activity of the oil palm fruit products could be an indication of shelf stability against microbial contamination and rancidity.